2016
DOI: 10.1128/aem.02266-15
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiota of Freshwater Fish and Freshwater Niches Contain Omega-3 Fatty Acid-Producing Shewanella Species

Abstract: Approximately 30 years ago, it was discovered that free-living bacteria isolated from cold ocean depths could produce polyunsaturated fatty acids (PUFA) such as eicosapentaenoic acid (EPA) (20:5n-3) or docosahexaenoic acid (DHA) (22:6n-3), two PUFA essential for human health. Numerous laboratories have also discovered that EPA-and/or DHA-producing bacteria, many of them members of the Shewanella genus, could be isolated from the intestinal tracts of omega-3 fatty acid-rich marine fish. If bacteria contribute o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 67 publications
(94 reference statements)
10
58
0
Order By: Relevance
“…A6 from ice‐storage common carp ( Cyprinus carpio L.) (Beaz‐Hidalgo et al, ). Another one (W9) was similar to previously described isolate from walleye ( Sander vitreus ) with no definite identification (Castillo, Gram, & Dailey, ; Dailey et al, ). Isolates currently described were quite different from Shewanella reported mainly from environmental and food samples.…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…A6 from ice‐storage common carp ( Cyprinus carpio L.) (Beaz‐Hidalgo et al, ). Another one (W9) was similar to previously described isolate from walleye ( Sander vitreus ) with no definite identification (Castillo, Gram, & Dailey, ; Dailey et al, ). Isolates currently described were quite different from Shewanella reported mainly from environmental and food samples.…”
Section: Discussionsupporting
confidence: 59%
“…We took into consideration sequences of reference strains as well as bacteria previously collected from freshwater fish. Comparison of S. putrefaciens 16S rRNA genes of tested isolates with the ones described by other authors (Beaz-Hidalgo et al, 2015;Dailey et al, 2016;Qin et al, 2012) showed high similarity (≥99.5%) between all isolates (Supporting Information Table S1; Figure 1). Despite that in some cases, the 16S rRNA gene sequence was insufficient for reliable species identification (Beaz-Hidalgo et al, 2015;Dailey et al, 2016;Janda & Abbott, 2014).…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations